Preparation method and application of amino-functionalized metal organic framework material

By preparing aminofunctional metal organic frame materials under normal temperature conditions, the problem of poor stability of existing materials in humid environments is solved, the material's acid, alkali and water resistance is achieved, and the material's acid, alkali and water resistance is shown to show efficient CO2 adsorption performance.

CN119591889AActive Publication Date: 2025-03-11SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411695649.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing metal organic frame materials have poor stability in humid environments and are difficult to meet the requirements for the stability of adsorbent materials in practical applications.

Method used

Adenine and copper nitrate trihydrate were dissolved in N,N'-dimethylacetamide, and a solution of carboxylic acid and potassium carbonate was added dropwise. After stirring and soaking in ethanol, an amino-functionalized metal organic frame material was obtained, and the final product was obtained by vacuum drying.

Benefits of technology

The preparation of aminofunctional metal organic frame materials under normal temperature conditions was achieved, with good acid, alkali and water resistance, and showed high CO2 adsorption selectivity and adsorption amount.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591889A_ABST
    Figure CN119591889A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an amino-functionalized metal organic framework material and application of the prepared material to separation of CO2 / N2 and CO2 / CH4. The preparation method comprises the following steps: dissolving adenine and copper nitrate trihydrate in N, N '-dimethylacetamide to obtain a first mixed solution; dissolving carboxylic acid and potassium carbonate in deionized water to obtain a second mixed solution; and adding the second mixed solution into the first mixed solution, carrying out stirring reaction, and carrying out vacuum drying on an obtained solid product to obtain the amino-functionalized metal organic framework material. The amino-functionalized metal organic framework material prepared by the invention has high CO2 adsorption selectivity and adsorption capacity, and also has good acid-resistant, alkali-resistant and water-resistant stability. The amino-functionalized metal organic framework material prepared by the preparation method disclosed by the invention is applied to industrial CO2 adsorption separation and has an excellent separation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas adsorption and separation, and in particular to a preparation method and application of an amino-functionalized metal organic framework material. Background Art

[0002] With the development of society and the upgrading of industrial technology, human energy demand is increasing day by day. However, the main energy source in the world is still fossil fuels, and sustainable new energy technologies still require a large amount of economic resources. The combustion of fossil fuels produces a large amount of carbon emissions, which causes the concentration of CO2 in the atmosphere to continue to rise, intensifies the greenhouse effect, and triggers a series of climate problems.

[0003] Metal-organic framework materials are a type of crystalline porous materials with a periodic network structure that are self-assembled by inorganic metal ions or metal clusters and organic ligands through coordination bonds. Compared with traditional porous materials including silica gel, porous carbon, zeolite molecular sieves, etc., metal-organic framework materials have advantages such as ultra-high specific surface area, rich structure and modifiable pore structure, and can play a good role in the field of CO2 gas adsorption capture and separation. For example, Cu-BTC (also known as HKUST-1) is one of the metal-organic framework materials with excellent adsorption performance for CO2 under normal temperature and pressure conditions. The adsorption amount of CO2 of this material can reach 7.0 mmol / g at 10°C and 100 kPa (P.Aprea, D.Caputo, N.Gargiulo, et al. Modeling carbon dioxide adsorption on microporous substrates comparison between Cu-BTC metal-organic framework and 13X zeolitic molecular sieve [J], J Chem Eng Data, 55 (2010) 3655-3661). However, in practical applications, water vapor is everywhere, and many metal-organic framework materials, including Cu-BTC, have very poor water vapor stability. When exposed to a humid environment, their metal-ligand coordination bonds are easily broken, resulting in framework collapse (NC Burtch, H. Jasuja, KS Walton, Waterstability and adsorption in metal-organic frameworks [J], Chem Rev, 114 (2014) 10575-10612). Therefore, it is urgent to prepare metal-organic framework materials with good stability to meet the requirements for the stability of adsorption materials in practical applications.

[0004] CN116925378A provides a method for preparing a CuIn metal organic framework material and its application in CO2 adsorption. The method uses 4'-(1H-tetrazolyl-5-yl)-[1,1'-biphenyl]-3,5-dicarboxylic acid as an organic ligand, and the CO2 adsorption capacity of the material is 3.0mmol / g. The patent uses a solvent thermal reaction to prepare the adsorption material, which has high requirements for equipment safety and there is room for optimization in process energy consumption. In addition, the organic ligand used in the patent has a complex structure and a high cost of raw materials.

[0005] CN117046450A provides a method for preparing a carbide slag-based metal organic framework material and its application in CO2 adsorption. The patent uses carbide slag with a CaO mass fraction of more than 90% and an organic ligand, square acid, to react by ball milling, obtains a solid powder after washing, and prepares an adsorption material after modification with tetraethylene pentamine. The CO2 adsorption capacity of the material reaches 2.89 mmol / g. The patent requires multiple steps of reaction to obtain the adsorption material, and the operation process is complicated. In addition, the corrosive organic amine used in the process will remain in the waste liquid, which is harmful to the environment.

[0006] In view of the above reasons, it is very necessary to develop an adsorption material and preparation method with good chemical stability, high CO2 selectivity and adsorption capacity. Summary of the invention

[0007] The present invention aims at the requirements of CO2 gas adsorption, capture and separation, and its primary purpose is to provide a method for preparing an amino-functionalized metal-organic framework material and its application in adsorbing low-concentration CO2 in gas. The amino-functionalized metal-organic framework material provided by the present invention has good selectivity and adsorption capacity for CO2.

[0008] The present invention is achieved through the following technical solutions:

[0009] A method for preparing an amino-functionalized metal organic framework material comprises the following preparation steps:

[0010] (1) dissolving adenine and copper nitrate trihydrate in N,N'-dimethylacetamide and stirring for 10 minutes to obtain a first mixed solution; dissolving carboxylic acid and potassium carbonate in deionized water and stirring for 10 minutes to obtain a second mixed solution;

[0011] (2) adding the second mixed solution obtained in step (1) dropwise to the first mixed solution, stirring and reacting for 36 h to 48 h to obtain a reaction product, filtering the reaction solution, and soaking and filtering the solid product in ethanol in turn to obtain a green solid powder;

[0012] (3) vacuum drying the solid powder obtained in step (2) to obtain an amino-functionalized metal organic framework material.

[0013] Preferably, in step (1), the molar ratio of adenine to copper nitrate trihydrate is 1:(0.5-5).

[0014] Preferably, in step (1), the carboxylic acid is one of succinic acid, glutaric acid, formic acid, acetic acid and propionic acid.

[0015] Preferably, in step (1), the volume ratio of deionized water to N,N'-dimethylacetamide is 1:(0.6-5).

[0016] Preferably, in step (1), the molar ratio of adenine:carboxylic acid:potassium carbonate is 1:(0.5-5):(0.2-2).

[0017] Preferably, in step (3), the vacuum drying refers to vacuum drying at 60°C to 100°C for 2h to 6h.

[0018] An amino-functionalized metal organic framework material is used in the separation of mixed gases containing CO2 and N2 or CO2 and CH4.

[0019] The amino-functionalized metal organic framework material is used as a CO2 selective adsorption material and is used to adsorb industrial CO2 at room temperature and normal pressure. The CO2 adsorption capacity is 2.83 to 4.72 mmol / g and it has good acid resistance, alkali resistance and water resistance stability.

[0020] The preparation method of the present invention and the obtained product have the following advantages and beneficial effects:

[0021] (1) The preparation method of the present invention is simple to operate, easy to implement, and has good reproducibility;

[0022] (2) Compared with the traditional solvothermal synthesis (above 100°C), the present invention performs material synthesis at room temperature, which is more energy-saving and safer;

[0023] (3) Compared with the existing amino-functionalized metal organic framework materials, the amino-functionalized metal organic framework materials prepared by the present invention have low cost, with the total price of organic ligands being about 600 yuan / kg, and have good acid resistance, alkali resistance and water resistance stability;

[0024] (4) The adsorbent material used in the present invention has high CO2 adsorption selectivity and adsorption capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The CO2 adsorption isotherm of the amino-functionalized metal organic framework material obtained in Examples 1-5 of the present invention;

[0026] Figure 2The CO2, CH4 and N2 adsorption isotherms of Cu-AD-SA obtained in Example 1 of the present invention at room temperature;

[0027] Figure 3 The CO2, CH4 and N2 adsorption isotherms of Cu-AD-FA obtained in Example 3 of the present invention at room temperature;

[0028] Figure 4 : CO2 / CH4 and CO2 / N2 adsorption selectivity curves of Cu-AD-SA obtained in Example 1 of the present invention;

[0029] Figure 5 : CO2 / CH4 and CO2 / N2 adsorption selectivity curves of Cu-AD-FA obtained in Example 3 of the present invention;

[0030] Figure 6 The PXRD spectrum of the amino-functionalized metal organic framework material obtained in Examples 1-5 of the present invention after acid immersion;

[0031] Figure 7 This is the PXRD spectrum of the amino-functionalized metal organic framework material obtained in Examples 1-5 of the present invention after being soaked in alkali;

[0032] Figure 8 This is the PXRD spectrum of the amino-functionalized metal organic framework material obtained in Examples 1-5 of the present invention after being soaked in deionized water. DETAILED DESCRIPTION

[0033] The following is a preferred embodiment of the present invention. It should be noted that a person skilled in the art may make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0035] Example 1

[0036] A method for preparing an amino-functionalized metal organic framework material, wherein the preparation of the adsorbent material comprises the following steps:

[0037] (1) 0.8 g of adenine (5.92 mmol, n1) and 1.6 g of copper nitrate trihydrate (6.62 mmol, n2) were dissolved in 30 mL of N,N'-dimethylacetamide and stirred for 10 min to obtain a first mixed solution; 0.7 g of succinic acid (5.93 mmol, n3) and 0.4 g of potassium carbonate (2.89 mmol, n4) were dissolved in 15 mL of deionized water and stirred for 10 min to obtain a second mixed solution;

[0038] (2) adding the second mixed solution obtained in step (1) to the first mixed solution, stirring the reaction for 36 hours to obtain a reaction product, filtering the reaction solution, and soaking and filtering the solid product in ethanol to obtain a green solid powder;

[0039] (3) The solid powder obtained in step (2) is placed at 60° C. and vacuum dried for 4 h to obtain an amino-functionalized metal organic framework material, which is recorded as Cu-AD-SA material. The material is then sealed and stored or its CO2 adsorption and removal performance is tested.

[0040] Example 2

[0041] A method for preparing an amino-functionalized metal organic framework material, wherein the preparation of the adsorbent material comprises the following steps:

[0042] (1) 0.8 g of adenine (5.92 mmol, n1) and 1.6 g of copper nitrate trihydrate (6.62 mmol, n2) were dissolved in 30 mL of N,N'-dimethylacetamide and stirred for 10 min to obtain a first mixed solution; 0.8 g of glutaric acid (6.05 mmol, n3) and 0.4 g of potassium carbonate (2.89 mmol, n4) were dissolved in 15 mL of deionized water and stirred for 10 min to obtain a second mixed solution;

[0043] (2) adding the second mixed solution obtained in step (1) to the first mixed solution, stirring the reaction for 40 hours to obtain a reaction product, filtering the reaction solution, and soaking and filtering the solid product in ethanol to obtain a green solid powder;

[0044] (3) The solid powder obtained in step (2) is placed at 80° C. and vacuum dried for 6 h to obtain an amino-functionalized metal organic framework material, which is recorded as Cu-AD-GA material. The material is then sealed and stored or its CO2 adsorption and removal performance is tested.

[0045] Example 3

[0046] A method for preparing an amino-functionalized metal organic framework material, wherein the preparation of the adsorbent material comprises the following steps:

[0047] (1) 0.8 g of adenine (5.92 mmol, n1) and 1.6 g of copper nitrate trihydrate (6.62 mmol, n2) were dissolved in 30 mL of N,N'-dimethylacetamide and stirred for 10 min to obtain a first mixed solution; 0.6 g of formic acid (6.52 mmol, n3) and 0.4 g of potassium carbonate (2.89 mmol, n4) were dissolved in 15 mL of deionized water and stirred for 10 min to obtain a second mixed solution;

[0048] (2) adding the second mixed solution obtained in step (1) to the first mixed solution, stirring the reaction for 48 hours to obtain a reaction product, filtering the reaction solution, and soaking and filtering the solid product in ethanol to obtain a green solid powder;

[0049] (3) The solid powder obtained in step (2) is placed at 100° C. and vacuum dried for 2 h to obtain an amino-functionalized metal organic framework material, which is recorded as Cu-AD-FA material, and then sealed and stored or the material's ability to adsorb and remove CO2 is tested.

[0050] Example 4

[0051] A method for preparing an amino-functionalized metal organic framework material, wherein the preparation of the adsorbent material comprises the following steps:

[0052] (1) 0.8 g of adenine (5.92 mmol, n1) and 1.6 g of copper nitrate trihydrate (6.62 mmol, n2) were dissolved in 30 mL of N,N'-dimethylacetamide and stirred for 10 min to obtain a first mixed solution; 0.8 g of acetic acid (6.67 mmol, n3) and 0.4 g of potassium carbonate (2.89 mmol, n4) were dissolved in 15 mL of deionized water and stirred for 10 min to obtain a second mixed solution;

[0053] (2) adding the second mixed solution obtained in step (1) to the first mixed solution, stirring the reaction for 42 hours to obtain a reaction product, filtering the reaction solution, and soaking and filtering the solid product in ethanol to obtain a green solid powder;

[0054] (3) The solid powder obtained in step (2) is placed at 60° C. and vacuum dried for 6 h to obtain an amino-functionalized metal organic framework material, which is recorded as Cu-AD-AC material, and then sealed and stored or the material's ability to adsorb and remove CO2 is tested.

[0055] Example 5

[0056] A method for preparing an amino-functionalized metal organic framework material, wherein the preparation of the adsorbent material comprises the following steps:

[0057] (1) 0.8 g of adenine (5.92 mmol, n1) and 1.6 g of copper nitrate trihydrate (6.62 mmol, n2) were dissolved in 30 mL of N,N'-dimethylacetamide and stirred for 10 min to obtain a first mixed solution; 0.9 g of propionic acid (6.07 mmol, n3) and 0.4 g of potassium carbonate (2.89 mmol, n4) were dissolved in 15 mL of deionized water and stirred for 10 min to obtain a second mixed solution;

[0058] (2) adding the second mixed solution obtained in step (1) to the first mixed solution, stirring the reaction for 48 hours to obtain a reaction product, filtering the reaction solution, and soaking and filtering the solid product in ethanol to obtain a green solid powder;

[0059] (3) The solid powder obtained in step (2) is placed at 60° C. and vacuum dried for 4 h to obtain an amino-functionalized metal organic framework material, which is recorded as Cu-AD-PA material. The material is then sealed and stored or its CO2 adsorption and removal performance is tested.

[0060] Test example:

[0061] a. Pore structure and specific surface area of ​​amino-functionalized metal organic framework materials:

[0062] The present invention uses the ASAP 2020 pore size analyzer produced by Micromeritics Corporation of the United States to test the pore structure of Cu-AD-SA, Cu-AD-GA, Cu-AD-FA, Cu-AD-AC, and Cu-AD-PA prepared in Examples 1-5 of the present invention. The results are shown in Table 1.

[0063] Table 1:

[0064]

[0065] As can be seen from Table 1, the BET specific surface area of ​​the amino-functionalized metal organic framework material prepared by the present invention is 732.3-1008.2 m 2 / g, with a total pore volume of 0.27-0.35cm 3 / g, and the pore size is in the range of 0.42-0.48nm, which indicates that the framework structure of the amino-functionalized metal-organic framework materials prepared in Examples 1-5 of the present invention is a microporous structure, and all have a high specific surface area and a large pore volume. In addition, the amino groups on the organic ligand adenine in the amino-functionalized metal-organic framework materials prepared by the present invention are all directed to the inside of the pores, and the pore size is small, slightly larger than the kinetic diameter of the CO2 molecule (0.33nm), which will help to improve the adsorption force of the amino-functionalized metal-organic framework materials on the CO2 molecules.

[0066] b. CO2, CH4 and N2 adsorption isotherms of amino-functionalized metal organic framework materials:

[0067] The present invention uses a 3-Flex full-function multi-purpose adsorption instrument produced by Micromeritics, USA, to test the gas adsorption isotherms of CO2, CH4 and N2 on the materials prepared in Examples 1 to 5 of the present invention. Before the sample is tested, it is placed at 80°C for vacuum degassing for 6 hours.

[0068] Figure 1 is the adsorption isotherm of CO2 on the amino-functionalized metal organic framework material prepared in Examples 1-5 of the present invention at 25°C. Figure 1 It is analyzed that at room temperature and pressure, the order of CO2 adsorption of amino-functionalized metal organic framework materials is Cu-AD-SA>Cu-AD-FA>Cu-AD-GA>Cu-AD-AC>Cu-AD-PA, and the adsorption of CO2 is 4.72, 4.59, 3.93, 3.82, and 2.83 mmol / g, respectively. It is worth noting that the amino-functionalized metal organic framework materials prepared in Examples 1-5 of the present invention all show preferential adsorption of CO2, and the adsorption of CO2 is relatively high, among which Cu-AD-SA shows the highest CO2 adsorption. For Cu-AD-SA and Cu-AD-FA with the highest CO2 adsorption, CH4 and N2 gas adsorption isotherm tests were carried out, and it was found that the adsorption of CO2 by Cu-AD-SA was 5.9 and 18.2 times of its adsorption of CH4 and N2, respectively, and the adsorption of CO2 by Cu-AD-FA was 5.6 and 17.8 times of its adsorption of CH4 and N2, respectively.

[0069] c. Adsorption selectivity of amino-functionalized metal organic framework materials Cu-AD-SA and Cu-AD-FA for CO2 and CH4, CO2 and N2:

[0070] For Cu-AD-SA and Cu-AD-FA, which have the highest CO2 adsorption capacity, according to their adsorption isotherm data of CO2, CH4, and N2 at 25 °C, such as Figure 2 and Figure 3 As shown, the ideal adsorption solution model was used to calculate their respective CO2 / CH4 and CO2 / N2 adsorption selectivities. Figure 4 This is the adsorption selectivity curve of Cu-AD-SA prepared in Example 1 of the present invention for CO2 / CH4 and CO2 / N2. Figure 4 It shows that the adsorption selectivity of Cu-AD-SA for CO2 / CH4 and CO2 / N2 first decreases and then increases with the increase of pressure. Figure 5 This is the adsorption selectivity curve of Cu-AD-FA prepared in Example 3 of the present invention for CO2 / CH4 and CO2 / N2. Figure 5It shows that the adsorption selectivity of Cu-AD-FA for CO2 / CH4 and CO2 / N2 first decreases and then increases with the increase of pressure. It is worth noting that at 100kPa, the adsorption selectivity of Cu-AD-SA for CO2 / CH4 and CO2 / N2 are 18.5 and 61.6 respectively, and the adsorption selectivity of Cu-AD-FA for CO2 / CH4 and CO2 / N2 are 34.3 and 82.2 respectively, both higher than Cu-AD-SA. This is because the CO2 adsorption amount of Cu-AD-FA at low pressure is slightly higher than that of Cu-AD-SA. The amino-functionalized metal organic framework material prepared by the present invention has high adsorption selectivity for CO2 / CH4 and CO2 / N2 because the framework has amino groups pointing to the pores, and the H atoms on the amino groups can produce strong electrostatic interactions with the O atoms in the CO2 molecules, but can only produce weak interactions with CH4 and N2 molecules. Therefore, the amino groups pointing to the pores in the amino-functionalized metal organic framework material prepared by the present invention can enhance the molecular adsorption force difference of the framework to CO2 / CH4 and CO2 / N2, and improve the adsorption selectivity of CO2 / CH4 and CO2 / N2.

[0071] d. Acid, alkali and water resistance of amino-functionalized metal organic framework materials:

[0072] The present invention uses a D8-ADVANCE fully automatic X-ray diffractometer of Bruker Company of Germany to characterize the crystal structure of Cu-AD-SA, Cu-AD-GA, Cu-AD-FA, Cu-AD-AC, and Cu-AD-PA prepared in Examples 1-5 of the present invention after stability testing. After soaking the five samples prepared in Examples 1-5 of the present invention in hydrochloric acid with pH=2, sodium hydroxide solution with pH=12, and deionized water for 1 week, the samples are taken out and scanned in the range of 5-50° at twice the diffraction angle, with a scanning step of 0.02°. The voltage and current used in the test are 40 kV and 40 mA, respectively, and Cu K α ray.

[0073] Figure 6-8 The PXRD spectra of Cu-AD-SA, Cu-AD-GA, Cu-AD-FA, Cu-AD-AC and Cu-AD-PA prepared in Examples 1 to 5 of the present invention after being treated with acid, alkali and deionized water. Figure 6-8It can be seen that the amino-functionalized metal-organic framework materials prepared in Examples 1-5 of the present invention have similar PXRD diffraction spectra. All materials have three characteristic diffraction peaks at twice the diffraction angle of 6.8, 13.2 and 13.7 degrees. These characteristic diffraction peaks are basically consistent with the characteristic diffraction peaks of the corresponding materials reported in the literature (L. Wang, K. Wang, H. An, et al. A hydrolytically stable Cu (II) -based metal-organic framework with easily accessible ligands for water harvesting [J], ACS Appl. Mater. Interfaces, 13 (2021) 49509-49518; L. Wang, J. Lv, Q. Ye, et al. Nanoporous Cu (II) -adenine-based metal-organic frameworks for selective adsorption of C2H2 from C2H4 and CO2 [J], ACS Appl.Mater.Interfaces, 6 (2023) 22095-22103), indicating that the target amino-functionalized metal-organic framework material was successfully prepared, and also indicating that the amino-functionalized metal-organic framework material prepared using the experimental conditions of Examples 1-5 has a similar crystal structure. In addition, the PXRD spectra of the five samples all showed narrow diffraction peaks and strong peak intensities, indicating that the five samples all had high crystallinity. It is worth noting that after being soaked in acid, alkali and deionized water, the PXRD spectra of the five samples remained unchanged, which shows that the treated samples still maintain the integrity of their frameworks, proving that the amino-functionalized metal-organic framework material prepared by the present invention has good acid, alkali and water resistance. Stability.

[0074] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an amino-functionalized metal organic framework material, characterized in that: The preparation of adsorbent materials includes the following steps: (1) dissolving adenine and copper nitrate trihydrate in N,N'-dimethylacetamide and stirring to obtain a first mixed solution; dissolving carboxylic acid and potassium carbonate in deionized water and stirring to obtain a second mixed solution; (2) adding the second mixed solution obtained in step (1) dropwise to the first mixed solution, stirring and reacting for 36 h to 48 h to obtain a reaction product, filtering the reaction solution, and soaking and filtering the solid product in ethanol in turn to obtain a green solid powder; (3) vacuum drying the solid powder obtained in step (2) to obtain an amino-functionalized metal organic framework material.

2. The method for preparing an amino-functionalized metal organic framework material according to claim 1, characterized in that: In step (1), the molar ratio of adenine to copper nitrate trihydrate is 1:(0.5-5).

3. The method for preparing an amino-functionalized metal organic framework material according to claim 1, characterized in that: In step (1), the carboxylic acid is selected from one of succinic acid, glutaric acid, formic acid, acetic acid and propionic acid.

4. The method for preparing an amino-functionalized metal organic framework material according to claim 1, characterized in that: In step (1), the volume ratio of deionized water to N,N'-dimethylacetamide is 1:(0.6-5).

5. The method for preparing an amino-functionalized metal organic framework material according to claim 1, characterized in that: In step (1), the molar ratio of adenine: carboxylic acid: potassium carbonate is 1: (0.5-5): (0.2-2).

6. The method for preparing an amino-functionalized metal organic framework material according to claim 1, characterized in that: In step (2), the soaking time is 2 hours to 24 hours.

7. The method for preparing an amino-functionalized metal organic framework material according to claim 1, characterized in that: In step (3), the vacuum drying is: vacuum drying at 60°C to 100°C for 2h to 6h.

8. An amino-functionalized metal organic framework material prepared by the method according to any one of claims 1 to 6, characterized in that: It can adsorb CO2 at room temperature and pressure, with the CO2 adsorption capacity of 2.83-4.72 mmol / g. It has good acid resistance, alkali resistance and water resistance stability.

9. The amino-functionalized metal organic framework material according to claim 8 is used for separation of mixed gas containing CO2 and N2.

10. The amino-functionalized metal organic framework material according to claim 8 is used for separation of mixed gas containing CO2 and CH4.

Citation Information

Patent Citations

  • Metal-organic framework material for efficient CO2 / N2 selective separation and adsorption and preparation method of metal-organic framework material

    CN106588960A

  • Amino acid @Cu-BTC composite adsorbent and preparing method thereof

    CN108339522A

  • Microporous Cu-MOF metal organic framework material constructed by adenine and auxiliary ligand, and preparation and application thereof

    CN110922606A

Cited By

  • Anti-aging antibacterial film and preparation method thereof

    CN120192610A

  • Aging-resistant antibacterial film and preparation method thereof

    CN120192610B

  • Flame-retardant B1-level sheath material and application thereof in cable

    CN120383793A

  • A flame-retardant b1 class sheath material and its use in cables

    CN120383793B

  • Environment-friendly sound-absorbing material for indoor decoration, preparation method and construction method based on environment-friendly sound-absorbing material

    CN121107745A